PENDIDIKAN AGAMA KRISTEN ANTISIPATIF RADIKALISME DALAM BERAGAMA DI INDONESIA - Fredik Melkias Boiliu; Noh Ibrahim Boiliu; Esther Rela Intarti (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2019)
This article is an attempt to include Christian religious education as religious education that is antipative to radicalism in religion in Indonesia. Indonesia is a diverse country in religion, in this case, there are religious names that are recognized in the Indonesian nation. The six religions are Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism. Religious radicalism is an act of a person or group of people that is contrary to humanitarian principles on the basis of religious beliefs. With a tendency to justify, support, or tolerate understandings or actions that are contrary to humanitarian principles on the basis of claims of religious understanding. Seeing this phenomenon, then to overcome it must be through teaching religious education. Christian religious education is an appropriate religious education to anticipate the understanding of religious radicalism that is happening and will occur in the life of the community, through teaching Christian religious education in families, churches, schools and plural societies Artikel ini merupakan upaya untuk memasukan pendidikan agama Kristen sebagai pendidikan agama yang antipatif terhadap radikalisme dalam beragama di indonesia. Indonesia merupkan Negara yang beragam dalam beragama, dalam hal ini, ada enama agama yang di akui di bangsa Indonesia keenam agama tersebut adalah Islam, Kristen, Katolik, Hindu, Budha, dan Konhucu. Radikalisme agama merupakan tindakan seseorang atau sekelompok orang yang bertentangan dengan prinsip-prinsip kemanusiaan atas dasar keyakinan agama. Dengan kecenderungan untuk membenarkan, mendukung, atau menoleransi paham atau tindakan yang bertentangan dengan prinsip-prinsip kemanusiaan tersebut atas dasar klaim paham keagamaan. Melihat fenomena tersebut, maka untuk mengatasinya harus melalui pengajaran pendidikan agama. Pendidikan agama Kristen merupakan pendidikan agama yang tepat untuk mengantisipasi paham radikalisme agama yang sedang terjadi dan yang akan terjadi dalam kehidupam masyarakat, melalui pengajaran pendidikan agama Kristen di keluarga, gereja, sekolah dan masyarakat majemuk.